Morphogenesis of the taxonomically significant microstructures of the siliceous cell wall of the diatom Aulacoseira granulata - Ye. D. Bedoshvili; K. V. Gneusheva; Ye. V. Likhoshway (Acta Biologica Sibirica, 2017)
This paper documents the process of the siliceous valve formation in diatom Aulacoseira granulata from Bratsk Reservoir (Irkutsk Region, Russia) reveals by scanning electron microscopy. It is shown that the shape of separating spines that facilitate colony splitting and species dispersal, as well as that of mucus-producing labiate processes, is determined during the early stages of the morphogenesis.